Novel strategy for ostial left anterior descending artery acute myocardial infarction: Combined treatment with directional coronary atherectomy followed by drug‐coated balloon angioplasty - Hiroyuki Yamamoto; Takahiro Sawada; Tomofumi Takaya; Hiroya Kawai; Yoshinori Yasaka (Clinical Case Reports, 2021)
Abstract A 69‐year‐old female diagnosed with ostial left anterior descending artery acute myocardial infarction underwent percutaneous coronary intervention using combined directional coronary atherectomy followed by drug‐coated balloon angioplasty. This report highlights a novel management strategy with no permanent scaffold left in the coronary artery.